Households' access to an improved latrine and its associated factors among households of sanitation marketing products users and non-users, Northeast Amhara, Ethiopia. Issue 11 (November 2022) - Asrate, Wendye; Admasie, Amha; Shibabaw, Tebkew
Abstract: Sanitation marketing is an approach to increase access to the improved latrine on a large scale which helps households to promote proper utilization of sanitary facilities. It helps to close the huge sanitation access gap in developing countries like Ethiopia. This study aimed to assess households' access to an improved latrine and its associated factors among sanitation marketing product users and non-users in Dessie Zuria District, Northeast Amhara, Ethiopia. A community-based comparative cross-sectional study was conducted among 640 households, in 2021. Multi-stage sampling techniques and a structured questionnaire were used. Data were checked, coded, and entered into Epi-info version 7 and exported to Statistical Package for Social Sciences version 23.0 for analysis. Binary logistic regression was employed to determine factors associated with improved latrine access. The study revealed that overall 59.8% of the households had access to improved latrines. Of this, 75.2% (95% Confidence Interval (CI): 70, 80) of households were Sanitation marketing products users; and 44.2% (95% CI: 39, 50) of households were from non-users of Sanitation marketing products. Being female household head, Adjusted Odds Ratio (AOR = 4.3, 95% CI: 1.69, 10.59); urban residence, AOR = 2.5, 95% CI: 1.23, 5.19; water access, AOR = 3.3, 95% CI: 1.63, 6.57 were significantly associated with access to the improved latrine in sanitation marketing products users households, while being a female household head, AOR = 7.3, 95% CI: 3.68, 14.39; urban residence, AOR = 2.8, 95% CI: 1.64, 4.77; water access, AOR = 2.4, 95% CI: 1.44, 4.10 were significantly associated with access to the improved latrine in non-user households of sanitation marketing products. Access to improved latrines is still a big problem in both households of sanitation marketing product users and sanitation marketing product non-users. Gender, residence, water access, supportive supervision, knowledge, and availability of sanitation hardware stores were found to be significant predictors of household access to an improved latrine. Hence, evaluating policies and strategies of sanitation marketing approach on improved sanitation facilities is recommended. Abstract : Improved latrine; Sanitation marketing; SaTo pan; Ducato; Sil Africa; Dessie Zuria.